Research advances in carbon-based electrode materials for electrosorptive separation of uranium from aqueous solutions - Tang, Ling; Wei, Tao; Wei, Yanfeng; Yu, Yin; Zhang, Haipeng (Frontiers in Materials, 2025)
Electrosorptive removal of uranium from aqueous solutions has emerged as an auspicious approach for mitigating radioactive pollution, with carbon-based materials serving as pivotal electrode components due to their exceptional conductivity, tunable surface chemistry, and structural versatility. This review thoroughly examines recent progress in carbon-based capacitive deionization (CDI) electrodes for U(VI) removal and systematically assesses critical modification approaches, including heteroatom doping, surface functional group modification, and metal oxide loading. Each strategy is critically examined regarding its underlying mechanism, material design principles, and influence on uranium adsorption capacity and selectivity. A particular emphasis is placed on synergistic effects from combined modification approaches, which consistently outperform single-component systems. Bridging insights from environmental science and energy storage technologies, this work proposes an integrated optimization framework that establishes fundamental structure-performance relationships for CDI electrodes. By systematically synthesizing current research progress while identifying key knowledge gaps, this review offers strategic guidance for the rational design of next-generation carbon-based materials to enable efficient, selective, and sustainable radioactive wastewater remediation.